Resiliensi Mahasiswa Ilmu Kesehatan Tingkat Pertama pada Masa Pandemi Covid-19 - Meivita Dewi Purnamasari; Keksi Girindra Swasti; Riski Ima Ramadani; Keksi Girindra Swasti (Journal of Bionursing, 2023)
Background. The Covid-19 pandemic has caused various changes, including the learning system in schools. Freshman students must adapt to these changes and go through a transition from high school to college. Resilience is needed by freshmen in order to get through this difficult time. This study aimed to find out the characteristics of the respondents, the level of resilience, and resilience based on the characteristics of the respondents. Methods. This research used a quantitative descriptive method. The research sample was 266 people who were taken using the Stratified Random Sampling technique. The instruments used are The Rugged Resilience Measure (RRM) to measure internal protective factors and The Child and Youth Resilience Measure-Revised (CYRM-R) to measure external protective factors. Results. The majority of respondents were female (77.8%) and majored in Nursing (24.4%). Student resilience is in the moderate category on internal (72.6%) and external (65.4%) protective factors. High resilience was found more in male respondents (40.7% internal and 30.5% external protective factors), Physical Education majors (31.4% internal and 21.6% external protective factors), and Pharmacy majors (external protective 21.6%). Conclusion. The resilience of first year students is in the moderate category in both internal and external protective factors. High resilience was found in the male sex, majoring in Physical Education, and Pharmacy major.